The global prevalence and associated risk factors of Eimeria infection in domestic chickens: A systematic review and meta‐analysis - Badri, Milad; Olfatifar, Meysam; Hayati, Alireza; Bijani, Behzad; Samimi, Rasoul; Abdoli, Amir; Nowak, Oskar; Diaz, Daniel; Eslahi, Aida Vafae (Veterinary medicine and science, 2024)
Background Eimeria is a protozoan parasite that affects poultry, particularly chickens, causing a disease known as coccidiosis. This disease imposes substantial significant economic challenges to the poultry sector. Objectives The current study aimed to estimate the global prevalence and associated risk factors of Eimeria in domestic chickens. Methods Multiple databases (Scopus, PubMed, ProQuest, Web of Science and Google Scholar) were searched for articles published until June 2023. The pooled prevalence was estimated using a random‐effects model with a 95% confidence interval. The statistical analysis was conducted using meta packages in R version (3.6.1). Results In total, 41 articles fulfilled the eligibility criteria. The global pooled prevalence was 44.3% (36.9%–51.8%) with Eimeria tenella (38.7%, 30.1%–47.7%) as the most prevalent species. The highest pooled prevalence was related to the Western Pacific Region (80.5%, 72.6%–87.3%) and urban areas (44.4%, 36.5%–52.6%). Moreover, areas with humid subtropical climates represent the highest overall prevalence (75.8%, 46.6%–95.9%). Conclusion The necessity for robust and innovative strategies for preventing and managing this disease cannot be overstated. Addressing Eimeria impact is crucial not only for safeguarding poultry health but also for sustaining the economic viability of the poultry industry. Coccidiosis caused by Eimeria parasites is a serious disease in chickens. It leads to diarrhoea, weight loss, decreased egg production and even death in severe cases. It poses substantial economic conflictions to the poultry sector. Preventing and managing this disease in poultry through a robust and innovative strategy is imperative. Regular monitoring and early intervention, along with proper hygiene, vaccination and use of medications, are essential to minimize the impact of the disease in chicken populations.